The role of p53 in liver fibrosis - Yu, Siyu; Ji, Guang; Zhang, Li (Frontiers in Pharmacology, 2022)
The tumor suppressor p53 is the central hub of a molecular network, which controls cell proliferation and death, and also plays an important role in the occurrence and development of liver fibrosis. The abundant post-translational processing and modification endow the functional diversity of p53. Considering the relationship between p53 and liver fibrosis, drug intervention targeting p53 or management of p53 regulation might be effective strategies to treat liver fibrosis. Here, we systematically discuss the regulation of p53 in different liver cells (hepatocytes, immune cells, HSCs, etc) and the role of p53 in the development of liver fibrosis, and propose possible interventions to prevent the pathogenic processes of liver fibrosis.